IMPLEMENTATION OF HEALTH IMPROVEMENT PROGRAM AT TECHNICAL UNIVERSITY - Sergey I. Kramskoy; Irina A. Amelchenko (Высшее образование в России)
The article explores the mechanisms of realization of the health-forming program in the learning process in the discipline “Physical training”. There are analyzed the problems of increasing students’ activity in organization of their own health training and exploration ofthe valuable potential of physical culture.